Hydro-visco-implantation Technique for Wound-assisted Foldable Intraocular Lens Implantation During Microincision Cataract Surgery - Erhan Özyol; Pelin Özyol (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2014)
The routine use of ophthalmic viscosurgical device (OVD) has revolutionized many anterior segment surgeries. All agents may be responsible for causing or exacerbating a transient, but occasionally significant, postoperative intraocular pressure (IOP) elevation, anterior chamber reaction. Removal of OVD from the anterior chamber is then very important. Otherwise administration of topical antiglaucomatous, steroid, or mydriatic drops may be needed in averting or controlling the increased IOP, inflammation, or synechiae [1,2]. Less use of OVD is preferable for both cost-effectiveness and easy removal from eye. Based on this knowledge we have described hydro-viscoimplantation technique that is including IOL implantation and passive removal of OVD.